Penerapan Model Pembelajaran Kooperatif Tipe TAPPS (Thinking Aloud Pair Problem Solving) Untuk Meningkatkan Prestasi Belajar Peserta Didik - Mita Elida Putri; Radjawaly Usman Rery; Sri Haryati (Program Pasca Sarjana UNM, 2019)
The research aims to improve students learning achievement on the subject of stoichiometric in the class X MIPA SMAN 2 Siak Hulu. This research method uses a quantitative approach. Data analysis using normality test, homogeneity test and analysis to test the hypothesis was using t-test right side. Based on the analysis of data processing obtained tcount > ttable is 2,33 > 1,67 means that the implementation of cooperative learning model TAPPS (Thinking Aloud Pair Problem Solving) can improve students learning achievement on the subject of stoichiometric in the class X MIPA SMAN 2 Siak Hulu with categories of achievement improvement learning in the experimental class based on Score (N-Gain) is high, which is 0.8.